Gestión educativa para la participación activa de la familia en el rendimiento académico en el Liceo de Colorado de Abangares (Innovaciones Educativas, 2019)
The article analyzes the educational management actions that reinforce the support of the family to ninth-year students to improve their academic performance. The study is carried out due to the low performance observed in high school exams at the Liceo de Colorado. To understand the problem, a series of external and internal factors that affect the academic performance must be taken into account, such as, for example, the socioeconomic situation, the support of the family, the management carried out by the educational center, among others. Among the main results, it was found that educational management is at a stage in which the family has not been integrated and makes a passive and assistance-based collaboration, which does not benefit academic performance. Therefore, the educational manager has the task of planning and implementing strategies that promote family integration to the educational center with active participation in order to increase student performance
Keywords: Educational management; academic achievement parent participation; family; active participation.